Usefulness and Limitation of Ultrasonography in the Diagnosis of Intestinal Intussusception in Cows - Sheikh Imran; S. P. Tyagi; Adarsh Kumar; Amit Kumar; Arvind Sharma; Shivali Sharma (Veterinary Medicine International)
The present study was conducted on 6 chronically ill Jersey/Red Sindhi cross-bred cows, which were suspected for intestinal obstruction on the basis of history and clinical signs. These cows were ultimately diagnosed with intestinal intussusception based on a combination of clinical, ultrasonographic and surgical examinations. “Bull’s eye lesion” was the most prominent ultrasonographic finding, diagnostic for intussusception either trans-abdominally or transrectally. Dilated intestinal loops greater than 3.1 cm (mean ± SE, 4.41 ± 0.25) were imaged in the lower flank and the 12th intercostal space on the right side. Ultrasonography proved to be a useful tool in supplementing and substantiating the transrectal findings in cases of the bovine intestinal intussusception. However, ultrasonography was not significantly helpful where transrectal examination of the cows did not reveal any suspected intestinal mass.